A new species of planthopper in the genus Patara (Hemiptera: Auchenorrhyncha: Fulgoroidea: Derbidae) from central Jamaica - Bahder, Brian W.; Myrie, Wayne; Helmick, Ericka E.; Bartlett, Charles R. (Zootaxa, 2024)
During survey work for planthoppers associated with palms in Jamaica, one new species of Patara was collected at the Castleton Botanic Garden and is here described as Patara euryfrons sp. n. The species is unusual in having a much broader head than is normally found in members of the genus. Supplementary molecular data for the barcoding region (5’ half) of the cytochrome c oxidase subunit I (COI), 18S rRNA gene and D9-D10 expansion region of the 28S rRNA gene is provided to support the placement of the novel taxon in Patara.